Literatur Review: Menginduksikan Nilai-Nilai Kebudayaan Sarolangun dalam Proses Layanan Konseling - Dwi Kurnia Sari; Affan Yusra; Erna Rahmawati Hatijah; Siti Sariyati; Uswatun Dwi Hasanah; Yodia Setiawati (Journal on Education, 2023)
The purpose of this literature is to describe the implementation of community customary marriages in Sarolangun Regency, to describe moral values in marriage, to describe the association of the Sarolangun people, to describe the communication of the Sarolangun people, and to describe the manners of the Sarolangun people. This study is a literature review. To achieve this goal, historical data have been collected through analysis of journals, scientific articles, and literature reviews. The results of his research are, firstly, the Inter-Customary Handling Event in Sarolangun-Jambi Regency is a place for men to bring souvenirs whose contents can be personal tools for the prospective wife to satisfy themselves with goods for both candidates. If the interpretation has a nominal value of Rp. 20,000,000.00 or other nominal value. Second, the moral values of the Sarolangun customary marriage are: (1) Moral values (hablumminallah), relating to God are reflected in their implementation which overlaps with religious teachings or belief in the One Almighty. Almighty. After choosing the right wife, religious requirements are followed and based on religious similarity. (2) Social moral values (Hablumminannat) are reflected in the stages of the traditional wedding ceremonies of the Sarolangun people. Jambi Regency include: Respect for others, Mutual respect for cooperation, Strengthening family relationships, Harmony, How to maintain customs in society, Respect, Individual moral values are their own moral values, which are reflected in the traditions of the Sarolangun-Jambi Regency community regarding marriage, including: Responsibility, Request for blessings, Independence, Obedience, Sacrifice, The Sarolangun-Jambi community association is a society that cultivates polite business with others and has fostered modern business.